EyeLax Enterprise / Mohd Adib Mohammed Taha ... [et al.] - Mohammed Taha, Mohd Adib; Mohamed Azhari, Khairul Annuar; Bin Abdullah, Abdul Hafiz; A.Rahim @ Jalil, Faizal Hilmy (Faculty of Mechanical Engineering, 2005)
EyeLax is a business Company that provides book holder as a stationary items. We runmng as a business trading.Our products are import from oversea. Our business will mostly catch our main target groups such as universities, schools, book store and Shopping complexs in area Selangor and Klang Valley.